Affinities of the Saw-billed Hermit (Ramphodon naevius) determined by cytochrome-b sequence data - Bleiweiss, Robert; Hendrickson, Sher L.; Berres, Mark E.; Willis, Yoshika O. [UNESP]; Willis, Edwin O. [UNESP] (Wilson Ornithological Society, 2003)
We sequenced 912 bp of the cytochrome-b gene to examine phylogenetic relationships of the enigmatic Saw-billed Hermit (Ramphodon naevius), a large and distinctive hummingbird endemic to tropical forests of southeastern Brazil. Bootstrapped maximum parsimony and maximum likelihood analyses of sequence data from 11 hummingbirds and several outgroups (two swifts, one goatsucker) support: (a) monophyly of the traditional hermit (Phaethornithinae) and nonhermit (Trochilinae) subfamilies, (b) placement of Ramphodon among hermits, and (c) a sister relationship between Ramphodon and an exemplar of the widespread polytypic hermit genus Glaucis. The association of Ramphodon with derived hermit lineages is concordant with subfamilial patterns of wing anatomy and nest architecture. However, the unusual plumages (striped underparts) and male bills (long, serrated, hooked) shared by Ramphodon and the Tooth-billed Hummingbird (Androdon aequatorialis) appear to have evolved within separate hermit and nonhermit tooth-billed clades. Distal placement of the Ramphodon-Glaucis clade within hermits implies that even distinctive Brazilian endemics such as Ramphodon are derived forms that evolved relatively recently.
Keywords: anatomy; genetic structure; phylogenetics; plumage; Brazil; South America; Androdon aequatorialis; Aves; Glaucis; Ramphodon; Ramphodon naevius; Trochilidae